Synthesis, Application and Biological Evaluation of Chemical Organic Compounds (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Discover the latest advancements in the world of chemical organic compounds with our Special Issue, "Synthesis, Application, and Biological Evaluation." Leading researchers have converged to showcase a diverse array of synthesized compounds, nanostructures, and extractions from plant and animal sources. Explore in silico analyses and biological assessments utilizing cutting-edge methodologies. Highlights: 1) Outstanding Antibacterial Activity: Chitosan/Fe(III)/deferoxamine nanoparticles outperform conventional drugs, showing promise in in vivo and in vitro applications. 2) Innovative Nanocomposites: Poly(o-anisidine)/BaSO4 nanocomposites exhibit potential antibacterial capabilities with tunable characteristics. 3) Novel Compounds: Discover N-acyl-α-amino acids, 4H-1,3-oxazol-5-ones, 2-acylamino ketones, and 1,3-oxazoles with remarkable antibacterial and antioxidant properties. 4) Anti-Inflammatory Agents: Explore hybrid molecules with enhanced anti-inflammatory and antioxidant activity, outperforming standard drugs. 5) Osteoporosis Prevention: Ethanolic extracts of G. littoralis show promise in preventing osteoporosis. 6) Perfume Longevity: Deuterated ambrox extends perfume shelf life, a fascinating innovation in the fragrance industry. This Special Issue represents the cutting edge of chemical research and applications, offering solutions to global challenges. Join us in the pursuit of knowledge and innovation regarding chemical organic compounds.